PENGARUH PROGRAM UKM TERHADAP CITRA PT PERKEBUNAN NUSANTARA V PEKANBARU - Sela Ginela Cherea Nata; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
UKM development is a Corporate Social Responsibility program carried out by PTPN V Pekanbaru to help UKM entrepreneurs in regencies and cities in Riau Province in order to develop their businesses.This study uses an explanatory quantitative approach with a questionnaire approach. The location of this research is Pekanbaru City, Riau. Sampling was done by Saturated Sampling (Census Sampling) where all population members were sampled and obtained a sample of 87 respondents.The coefficient of determination (R2) obtained is 0.030 and the coefficient of determination (Rsquare) is 0.030, meaning that the Effect of the UKM Program on Image of PT Perkebunan Nusantara V Pekanbaru is 3%. While the remaining 97% is influenced by other variables not included in this study. This means that the influence of the 3% UKM Program on Image of PT Perkebunan Nusantara V Pekanbaru has a very weak influence and based on the results of tcount (-1,628) <t table (1,988) with the resulting significance value of 0,107 still above 0.05, then H0 be accepted. This means that the regression coefficient is not significant. From the information, it can be concluded that the SME Program does not affect the Image.